The influence of conventional and novel blanching methods on potato granules, phytochemicals, and thermal properties of colored varieties - Saini, Rajni; Kaur, Sukhpreet; Aggarwal, Poonam; Dhiman, Atul (Frontiers in Nutrition, 2023)
Colored potatoes comprise many bioactive compounds that potentially support human health. Pretreatments like blanching affect these bioactives. This study aimed to explore the effects of different blanching methods (steam blanching, hot water blanching, and microwave-assisted blanching) on phytochemical as well as structural aspects of PP-1901 and Lady Rosetta(LR) potato varieties. Changes in antioxidant activity, colour, total ascorbic acid, phenolic and flavonoid content were based on the variations in parameters including temperature (blanching using hot water and steam), and capacity 100–900 W (blanching using microwave). For both PP-1901 and LR varieties, all the blanching methods led to significant reduction in residual peroxidase activity along with affecting their colour.The preservation of bioactive substances exhibited microwave>steam>hot water blanching trend. Blanching significantly increased the antioxidant activity of all the samples. Additionally, Fourier transform infrared spectroscopy revealed that phytocompounds were retained to their maximum in microwave blanched samples, specially at 300 W. Thermal analysis revealed that type of blanching method had significant impact on gelatinization temperature of potato. The process of blanching, which thought of as intermediate stage for many food items, will be explained by the current study.